Fatty acid profiling and physiochemical characterization of Chlorella sorokiniana potentially used for biofuel production - Muhammad Ammar; Omer, Maria; Aman, Sitwat; Abdul Hameed; Abbas, Safdar; Shaheen, Shabnam; Abbas, Aiman; Shakeel, Samina N (Penerbit Universiti Kebangsaan Malaysia, 2022)
Rising oil prices and climate change have resulted in more emphasis on research into renewable biofuels. In this study, different water samples were collected from local vicinities for the isolation of local isolates of microalgae to check their potential towards the production of biofuel by the addition of different chemical substrates. Five different concentrations of ascorbic acid and iron (III) chloride (0, 1, 2.5, 5 & 10 µM) are used as substrates. Microscopic analysis evaluated that samples belong to genus Chlorella and further molecular identification showed that the samples are C. sorokiniana. Among all the concentrations of ascorbic acid 2.5 µM is most effective against the C. sorokiniana strain 1 (Safari Wildlife Park, Lahore) and C. sorokiniana strain 2 (Bahria Town, Lahore) while C. sorokiniana Strain 3 (SukhChane Society, Lahore) responded at 2.5 & 5 µM in term of biomass production. FeCl3 (2.5 µM) is effective against C. sorokiniana strain 1 while the growth of C. sorokiniana strain 2 and C. sorokiniana Strain 3 is inhibited. Lipid content analysis showed that only the C. sorokiniana strain 1 shows effective results at 1 & 2.5 µM of ascorbic acid and FeCl3 , respectively. Those concentrations which give the significant results of lipid production were preceded for fatty acid profiling. Results indicate that the C. sorokiniana strain 1 can be considered as a source of alpha-linolenic acid; the basic constituent of biofuel production. In this study, it is concluded that C. sorokiniana strain 1 is useful for the production of environment friendly biofuel.